Detection of somatic copy number deletion of the CDKN2A gene by quantitative multiplex PCR for clinical practice - Tian, Yuan; Zhou, Jing; Qiao, Juanli; Liu, Zhaojun; Gu, Liankun; Zhang, Baozhen; Lu, Youyong; Xing, Rui; Deng, Dajun (Frontiers in Oncology, 2022)
Background: While the amplification of oncogenes (such as EGFR, c-ERBB2, c-MYC, and c-MET) are increasingly driving decision-making for precise cancer treatments, a feasible method to detect somatic copy number deletion (SCND) of tumor suppressor genes is still absent to date. Methods: The genomic coordinates of gene deletion fragments were analyzed using the Catalogue Of Somatic Mutation In Cancer (COSMIC) datasets. Interstitial base-resolution deletion/fusion coordinates for CDKN2A were extracted from published articles and our whole genome sequencing (WGS) datasets. The copy number of the CDKN2A gene was measured with a multiplex quantitative PCR assay P16-Light and confirmed with whole genome sequencing (WGS). Results: Estimated common deletion regions (CDRs) were observed in many tumor suppressor genes, such as ATM, CDKN2A, FAT1, miR31HG, PTEN, and RB1, in the SNP array-based COSMIC datasets. A 5.1 kb base-resolution CDR could be identified in >90% of cancer samples with CDKN2A deletion by sequencing. The CDKN2A CDR covers exon-2, which is essential for P16INK4A and P14ARF synthesis. Using the true CDKN2A CDR as a PCR target, a multiplex quantitative PCR assay P16-Light was programmed to detect CDKN2A gene copy number. P16-Light was further confirmed with WGS as the gold standard among cancer tissue samples from 139 patients. Conclusion: CDRs are common in many tumor suppressor genes. The 5.1 kb CDKN2A CDR was found in >90% of cancers containing CDKN2A deletion. The CDKN2A CDR was used as a potential target for developing the P16-Light assay to detect CDKN2A SCND and amplification for routine clinical practices.